Peran Kepemimpinan di Era Society 5.0 dengan Konsep Multieduhealthtainment - Diana, Aan; Soeratin, Harry (MASALIQ, 2023)
This article aims to analyze the role of leadership in the Society 5.0 era. with the Multieduhealthtainment concept marked by the convergence between technology, education, health, and entertainment. Leadership has a crucial role to play in addressing the complex and diverse challenges of an increasingly connected society. This study uses a qualitative approach by combining literature reviews and case studies. The results of this study reveal that effective leadership in the Society 5.0 era with the Multieduhealthtainment conception involves the ability to manage change, facilitate collaboration, inspire innovation, and build strong relationships in complex and dynamic contexts.